PENGEMBANGAN BAHAN AJAR E-MODUL BERBASIS CANVA SUBTEMA MANUSIA DAN LINGKUNGAN - Putry Salsa Bilah; Sandi Budiana; Yuli Mulyawati (STKIP Subang, 2022)
This study aims to determine the development of a Canva-Based E-Module on the Environmental Theme of Our Friends, the Sub-theme of Humans and the Environment in class VB SDN 1 Nagrak, Sukabumi Regency and to determine the feasibility of Canva-based E-Modules in the learning process. The method used in ths research is using the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). In this study, validation tests were carried out on experts in their fields (media experts, language experts, material experts) to develop and refine Canva-based E-Module products. The data results from the media expert validation were 93.75%, which means it was very feasible to implement. The linguist obtained a result of 90%, which means it is very feasible to implement, and the results of the material expert obtained a score of 100%, which means it was stated to be very feasible to implement, and based on a limited trial conducted on VB class students as many as 45 students obtained a score which is suitable for use is 83.43%, which means that this Canva-based E-Module product is suitable for use in the learning process.